Geodynamics of basins above subducted slabs: An integrated modelling study of tectonics, sedimentation, and magmatism in the Timok Magmatic Complex - Stojadinović Uroš; Toljić Marinko; Trivić Branislav; Pantović Radoje; Srećković-Batoćanin Danica; Krstekanić Nemanja; Kostić Bojan; Velojić Miloš; Stefanović Jelena; Ranđelović Nikola; Maleš Maja (Geološki Anali Balkanskoga Poluostrva)
Volcano‐sedimentary basins located in the orogenic hinterland area overlying subducted slabs are observed worldwide to be driven by the switching tectonic regimes induced by the changing mechanics of the slab. Despite many qualitative studies, the quantitative link between the subducted slab’s mechanics and the overlying basins’ evolution is less understood. Among the many examples observed worldwide, the Timok Magmatic Complex (TMC) in Serbia represents an optimal natural laboratory due to the complex tectonic setting during the various stages of the Middle Jurassic–Paleogene evolution of the subduction system. The TMC is a segment of the larger Late Cretaceous Apuseni‐Banat‐Timok‐Srednogorie (ABTS) magmatic belt, formed in response to the evolution of the subducted Mesozoic Neotethys oceanic slab beneath the Carpatho‐Balkanides of south‐eastern Europe. The TMC basin, with the associated intrusive and extrusive magmatics and volcano‐sedimentary deposits, represents an excellent area for a process‐oriented study on the interplay between tectonics, sedimentation, and magmatism in the basins above evolving subducted slabs. Within the scope of the newly funded TMCmod project, coupled field and laboratory kinematic and petrological investigations will be focused on creating a conceptual definition of the TMC geodynamic evolution, by combining near‐surface observations with the known evolution of the subduction system. This definition will be subsequently validated through analogue modelling and integrated into a coherent geodynamic model of tectonic switching in basins driven by the evolution of subducted slabs. The new model of the TMC basin’s geodynamic evolution will quantitatively advance the strategy of prospecting and exploration of world‐class porphyry copper‐ gold deposits, which have been actively exploited in this region for more than a century. Furthermore, reconstructed regional kinematic evolution will improve seismic hazard assessment during industrial and societal infrastructure planning and construction.